Pengembangan E-Modul Discon Berbasis Android (E-Modul Disroid) pada Materi Cahaya bagi Siswa Sekolah Dasar - Pratiwi, Indah; Azizah, Azizah; M.Akbar, Siti Zulqaidah; Pratama, Ryan Andhika; Sitepu, Melyani Sari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Changes from age to age in human life indirectly encourage humans to follow the times where it cannot be denied that all things are based on technology, including the world of education. The problem in this research is the change in the learning process carried out online with the help of development technology. The online learning process makes students difficult, especially in science learning, where learning is mostly carried out with practicum. The purpose of this study is to develop a valid and practical Android-based Discon E-Module. This research is a research and development (Research and Development) with a 4D model consisting of 4 stages, namely define, design, develop, and disseminate. The population in this study were fourth-grade students of Elementary School Inpres 1 Tondo. The research instrument used tests and media validation questionnaire sheets, material validation, and user validation. Based on the results of data analysis, it was obtained that the media validity was in the very good category, the material validity was in the good and very good categories, and user satisfaction was in the very good category. So it can be concluded that the Android-based E-Modul Discon (E-Modul Disroid) that was developed is included in the very valid and very practical criteria. So that this module can be used in science learning, especially for practical activities in grade IV elementary.